2003
DOI: 10.1167/iovs.02-0631
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Activates the TM ELAM-1/IL-1/NF-κB Response: A Potential Mechanism for Intraocular Pressure Reduction after Phacoemulsification

Abstract: A potentially IOP-lowering stress response is induced in TM cells by ultrasound. The findings suggest that this response may be induced clinically during cataract removal by phacoemulsification, and may be one mechanism responsible for the reduction in IOP that often follows this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 23 publications
(24 reference statements)
0
67
0
3
Order By: Relevance
“…Trabecular endothelial remodeling in response to ultrasonic stress, 27 prostaglandin release, 28 and increase in aqueous outflow by expansion of the trabecular meshwork 4 are some of the hypothetical mechanisms, but angle and ACD change induced by cataract removal has been shown to be the main mechanism of IOP change in OAs as well as NAs. 14 Huang et al 9 supported this hypothesis by showing that IOP reduction was associated with angle widening in both OA and NA eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Trabecular endothelial remodeling in response to ultrasonic stress, 27 prostaglandin release, 28 and increase in aqueous outflow by expansion of the trabecular meshwork 4 are some of the hypothetical mechanisms, but angle and ACD change induced by cataract removal has been shown to be the main mechanism of IOP change in OAs as well as NAs. 14 Huang et al 9 supported this hypothesis by showing that IOP reduction was associated with angle widening in both OA and NA eyes.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition, in cultured trabecular meshwork (TM) cells, phacoemulsification ultrasound upregulates interleukin IL-1a and endothelial leukocyte adhesion molecule-1, 7 suggesting potential effects of IL-1a on IOP reduction after phacoemulsification. On the other hand, our previous study showed that aqueous humor obtained from eyes with open-angle glaucoma contained increased monocyte chemoattractant protein-1 (MCP-1)/CC chemokine ligand 2 and IL-8 levels after phacoemulsification.…”
Section: Resultsmentioning
confidence: 99%
“…Poley et al suggest that lens removal allows the posterior capsule to move posteriorly, dislodging the zonula over the ciliary body with a consequent widening of Schlemm's canal and aqueous humour drainage improvement [12]. Another theory suggests that ultrasound energy used for phacoemulsification procedure is responsible for a sudden rise of pressure in the anterior chamber, producing inflammatory cytokines (mostly IL-1) that stimulate metalloproteinase production and trabecular meshwork remodelling, facilitating humour drainage [13].…”
Section: Discussionmentioning
confidence: 99%